2022
DOI: 10.3389/fnut.2022.1007885
|View full text |Cite
|
Sign up to set email alerts
|

Modified Nutrition Risk in Critically ill is an effective nutrition risk screening tool in severely burned patients, compared with Nutrition Risk Screening 2002

Abstract: ObjectiveThe present study aimed to evaluate the value of Modified Nutrition Risk in Critically ill (mNUTRIC) and Nutrition Risk Screening 2002 (NRS2002) in the prognosis of severely burned patients.MethodsThe retrospective cohort study used medical data of severely burned patients admitted to the burn center of Shanghai Ruijin Hospital between January 2015 and September 2021. Demographics, clinical characteristics, laboratory nutritional indicators, mNUTRIC score and NRS2002 score were collected and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
3
4
Order By: Relevance
“…Our study results are similar to those of other studies. However, unlike studies involving NRS-2002, the mNUTRIC score was the only screening tool that showed validity in discriminating patients at high risk of 28-day mortality in our study (23,31,32). In particular, NRS-2002 showed an unfair prediction for 28-day mortality (AUC at days 2 and 7, 0.505 and 0.548, respectively), which was significantly lower than that reported by Majari et (31,32).…”
Section: Prognostic Performance Of Mnutric Score For 28-day Mortalitycontrasting
confidence: 93%
See 2 more Smart Citations
“…Our study results are similar to those of other studies. However, unlike studies involving NRS-2002, the mNUTRIC score was the only screening tool that showed validity in discriminating patients at high risk of 28-day mortality in our study (23,31,32). In particular, NRS-2002 showed an unfair prediction for 28-day mortality (AUC at days 2 and 7, 0.505 and 0.548, respectively), which was significantly lower than that reported by Majari et (31,32).…”
Section: Prognostic Performance Of Mnutric Score For 28-day Mortalitycontrasting
confidence: 93%
“…However, unlike studies involving NRS-2002, the mNUTRIC score was the only screening tool that showed validity in discriminating patients at high risk of 28-day mortality in our study (23,31,32). In particular, NRS-2002 showed an unfair prediction for 28-day mortality (AUC at days 2 and 7, 0.505 and 0.548, respectively), which was significantly lower than that reported by Majari et (31,32). Although the NRS-2002 is recommended for use in various populations, one of the limitations of the use of this tool in ICU patients is related to the low cutoff value in terms of disease severity (APACHE II ≥ 10), which can lead to overestimation of high nutrition risk in the ICU (7,23).…”
Section: Prognostic Performance Of Mnutric Score For 28-day Mortalitycontrasting
confidence: 59%
See 1 more Smart Citation
“…Our study results are similar to those of other studies. However, unlike studies involving NRS-2002, the mNUTRIC score was the only screening tool that showed validity in discriminating patients at high risk of 28-day mortality in our study [23,31,32]. In particular, NRS-2002 showed an unfair prediction for 28-day mortality (AUC at days 2 and 7, 0.505 and 0.548, respectively), which was significantly lower than that reported by Majari et al (AUC 0.695) and Ma et al (AUC 0.726) [31,32].…”
Section: Prognostic Performance Of Mnutric Score For 28-day Mortalitycontrasting
confidence: 59%
“…However, unlike studies involving NRS-2002, the mNUTRIC score was the only screening tool that showed validity in discriminating patients at high risk of 28-day mortality in our study [23,31,32]. In particular, NRS-2002 showed an unfair prediction for 28-day mortality (AUC at days 2 and 7, 0.505 and 0.548, respectively), which was significantly lower than that reported by Majari et al (AUC 0.695) and Ma et al (AUC 0.726) [31,32]. Although the NRS-2002 is recommended for use in various populations, one of the limitations of the use of this tool in ICU patients is related to the low cutoff value in terms of disease severity (APACHE II ≥ 10), which can lead to overestimation of high nutrition risk in the ICU [7,23].…”
Section: Prognostic Performance Of Mnutric Score For 28-day Mortalitycontrasting
confidence: 59%